Adhesion of a water droplet on inclined hydrophilic surface and internal fluidity. (January 2020) - Al-Sharafi, Abdullah; Yilbas, Bekir S.; Ali, Haider; Al-Qahtani, H.
Abstract: A water droplet attachment on a hydrophilic surface with inclination is investigated. The influence of droplet size and the inclination angle of the surface on the droplet adhesion are examined. Height and lateral extension of the droplet on the inclined hydrophilic surface are formulated and the findings are compared with the experimental data. The hydrodynamic response of the droplet due to inclination of the surface is simulated and the flow field inside the droplet is predicted for various droplet inclination angles of the surface and the droplet size. An experiment is designed to validate the flow field predicted inside the droplet via incorporating particle image velocimetry (PIV). It is found that the velocity predicted agrees well with the PIV data. A circulation cell is developed inside the droplet and the rotational center and the strength of the fluid circulation change with the inclination angle and the droplet size. The adhesion force increases with increasing inclination angle of the surface and the droplet size. The shear force generated at the wetted surface contributes to the adhesion force; however, this contribution is not significant.